The Typicality of the Agri-Food Product Driver of the Enhancement of Destination Tourism The Apulian Case History - Pierluigi, Passaro; Di Vittorio , Arianna (European Scientific Journal, ESJ, 2022)
Typical products are becoming more and more an element of differentiation and qualification of entire territories, becoming one of their resources or, in some cases, the main resource and the real tourist attraction factor of the tourist resorts that direct their own promotion strategies of the territory to the new segments of tourist demand (tourists of taste or gastronauts, green tourists). In this sense, it becomes essential to activate synergies and commercial relations with the local economic system (for example with catering, trade, crafts) in order to actively consolidate the ancient territorial link, strengthening its image among consumers: thus, effectively serving as a promotional tool and enjoying the benefits derived from such approaches. Objective of the paper: "Indeterminacy" is the term that characterizes the concept of typicality of the agri-food product and that arises from the low level of information either of consumers and producers of agricultural raw materials and other operators in the supply chain. This work aims to analyze how much the knowledge and impact of the typical Apulian agri-food product affects the choice of the tourist destination. Methodology: The work is based on the analysis of data resulting from a survey in 2020 aimed at potential buyers of the agri-food product aimed at understanding the impact of the typical Apulian agri-food product in the choice of tourist destination. Results: The analysis carried out highlighted how the knowledge, awareness and enhancement of typical products represent a strong attractive lever for tourist flows, with a view to choosing the potential final destination. From the testimonies of the users and internal stakeholders it was clear that the typicality has not affected the value of the destination, which remains primary in the purchase intentions of potential customers, but has triggered a climb in the hierarchy of preferences of those who intend to live an experience Italian or foreign tourists, in fact, evaluate the offer enriched by the multiple nuances of the territorial tradition within a specific tourist route. Research limits: This work is intrinsically limited by the strictly qualitative nature of the survey, as well as by the analysis of a single case study. Originality: The originality of the study lies in the contribution it intends to provide to the advancement of research focused on the analysis based on the connection among the territory, typical products and tourist flows.